The Penderwicks at last [compact disc, unabridged] - Birdsall, Jeanne (Birdsall, Jeanne. Penderwicks series, 2018)
Nine years, five older siblings, a few beloved dogs, and an endless array of adventures--these are the things that have shaped Lydia's journey since readers first met her in The Penderwicks in Spring. Now it's summertime, and eleven-year-old Lydia is dancing at the bus stop, waiting for big sister Batty to get home from college. This is a very important dance and a very important wait because the two youngest sisters are about to arrive home to find out that the Penderwicks will all be returning to Arundel this summer, the place where it all began. And better still is the occasion: a good old-fashioned, homemade-by-Penderwicks wedding.